Nineteenth-Century African American Narratives in Britain and Ireland - Bernier, Celeste-Marie (Edinburgh University Press, 2025)
This is the first scholarly anthology of nineteen narratives written by African American authors and published in Britain and Ireland in the nineteenth century. These literary works share the powerful life stories of inspirationally pioneering writers: Charles Freeman, Phebe Ann Jacobs, Benjamin Crompton Chisley/William Jones, John Hart, John Williams, Henry (surname unknown), James Watkins, William Gustavus Allen, John Comber, Sarah Parker Remond, James Cheeney Thompson, Dinah Hope Browne, John Sella Martin, Lewis Smith, James Alfred Johnson, D. E. Tobias and Benjamin William Brown. Their narratives are reproduced alongside an in-depth introductory essay, author biographies, scholarly annotations and a detailed bibliography. All these authors testify to their lifelong ‘fight for freedom’ across their radical and revolutionary works. Throughout their lives, they warred against the ‘sufferings and horrors’ of enslavement as a centuries-old ‘cursed institution.’ ‘Words are weapons’ in their fight for Black liberation. Across their life’s works, they protested against the rise of the ‘spirit of slavery’ in white supremacist and white racist American and British transatlantic societies.